Analysis Of Critical Load Of Multilayered/gradient Cralsin Pvd Coatings Measured Using Scratch Tests - Washington Martins da Silva Júnior (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2018)
In stamping process, sliding between metal sheet and forming tool leads to wear of tool surface. Maintenance of stamping tools involves polishing the tool edge, or, in case of severe damage, replacement of the tool. Hard coatings have been applied on the stamping tool surfaces in order to reduce the maintenance cost causing a great economic impact in metal work industry. In this work, CrAlSiN coatings were applied by PVD onto SRV2W tool steel. The coating toughness was avaliated by the critical load in scratch tests. The following coating parameters were analyzed: 1- substrate surface finishing process; 2- coating architecture (multilayer or gradient); 3- chemical composition of the coating. AlSi concentration varied from the substrate/coating interface to the surface. Coatings were 3 µm thick. Scratch tests were carried out using a Vickers indenter. The applied normal load was varied from 0 to 13 N for a scratch length of 5 mm. In order to study the effect in the toughness, the substrate roughness was controlled by the finishing process before PVD coating. Samples subjected to polishing presented highest critical loads. Gradient coatings presented higher critical loads than those with a multilayer architecture. Coatings with higher concentration of AlSi near the surface supported higher loads before failure.